2021
DOI: 10.1155/2021/5937250
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy for Treating Chronic Low Back Pain: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Objective. To assess the effectiveness and safety of extracorporeal shockwave therapy (ESWT) for the treatment of chronic low back pain (CLBP). Methods. This was a systematic review and meta-analysis of randomized controlled trials (RCTs) designed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement standard. We identified relevant studies by searching multiple electronic databases, trial registries, and websites up to April 30, 2021, and examining reference lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
(45 reference statements)
0
20
0
4
Order By: Relevance
“…According to our information, there was only one previous meta-analysis about the application of ESWT in CLBP, but we found that this study had high heterogeneity in both pain and dysfunction index analyses, and no subgroup analysis or sensitivity analysis was conducted [27]. In addition, we found that this previous meta-analysis included an unpublished master's thesis and a study of participants with postpartum low back pain that may have affected the reliability of the results and were excluded from our study.…”
Section: Discussionmentioning
confidence: 95%
“…According to our information, there was only one previous meta-analysis about the application of ESWT in CLBP, but we found that this study had high heterogeneity in both pain and dysfunction index analyses, and no subgroup analysis or sensitivity analysis was conducted [27]. In addition, we found that this previous meta-analysis included an unpublished master's thesis and a study of participants with postpartum low back pain that may have affected the reliability of the results and were excluded from our study.…”
Section: Discussionmentioning
confidence: 95%
“…The 22 studies comprised 13 [9][10][11]14,17,20,[24][25][26][27][28][29][30] in Chinese and 9 in English, 20 [1][2][3][4][5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33][34][35] were journal articles, 2 [14,27] were www.md-journal.com master's theses, and 1749 patients were involved, with 881 and 868 patients in the experimental and control groups, respectively. Twenty-two studies were RCTs, all of which stated that "there was no statistically significant difference between the baseline of the experimental group and control group (P > .05)."…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Shockwave therapy is a novel conservative method of treatment for musculoskeletal pain produced by a range of illnesses [9] . Since it inhibits pain transmission and suppresses the inflammatory response, it is considered a good choice for alleviating lumbo-pelvic pain and enhancing its function in recent years [10][11][12] . Although menopause is a difficult time for most women and its symptoms have a significant influence on their well-being and life quality [13] , research regarding the benefit of physical therapy interventions on postmenopausal sacroiliac joint pain is lacking.…”
Section: Introductionmentioning
confidence: 99%